Mathematical modelling of solar drying of apricots in thin layers - Togrul, IT; Pehlivan, D (Elsevier Sci Ltd, 2002)
Solar drying experiments in thin layers of apricots grown in Elazig, Turkey, were conducted. An indirect forced convection solar dryer consisting of a solar air heater with conical concentrator and a drying cabinet were used in the experiments. Air was forced into the solar air heater by a blower and hot air obtained there was passed over the apricots. The changes in the mass of apricots and principal drying parameters were recorded continuously from morning to evening in each test day. Drying curves obtained from the data were fitted to a number of mathematical models and the effects of drying air temperature, velocity and relative humidity on the model constants and coefficients were evaluated by the multiple regression and compared to previously given models. The logarithmic drying model was found to satisfactorily describe the solar drying curve of apricots with a correlation coefficient (r) of 0.994. The constants and coefficients of this model could be explained by the effect of drying air temperature, velocity and relative humidity with a correlation coefficient (r) of 1.000. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: conical concentrator; solar dryer; apricot; modelling; statistical analysis